Changes in value added per person in selected industries in India, 1946 to 1969 - Kansal, S. M. (New Delhi : Economic and Scientific Research Foundation, 1975)
The study analyses changes in the value added per person in selected industries in India for the period 1946 to 1969. It also attempts to compare value added per employee in selected countries in broad groups of industries during the period 1963 to 1969
osc 06/12/2018
Loans
Keywords: Labor productivity; Industries